2007
DOI: 10.1038/nm1570
|View full text |Cite
|
Sign up to set email alerts
|

Sema3a maintains normal heart rhythm through sympathetic innervation patterning

Abstract: Sympathetic innervation is critical for effective cardiac function. However, the developmental and regulatory mechanisms determining the density and patterning of cardiac sympathetic innervation remain unclear, as does the role of this innervation in arrhythmogenesis. Here we show that a neural chemorepellent, Sema3a, establishes cardiac sympathetic innervation patterning. Sema3a is abundantly expressed in the trabecular layer in early-stage embryos but is restricted to Purkinje fibers after birth, forming an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
209
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(225 citation statements)
references
References 42 publications
15
209
1
Order By: Relevance
“…Those results or ours suggest that SNS abnormality is more sensitive for predicting arrhythmic events than is left ventricular dysfunction or structural heart disease. Our results may support the possibility that SNS activity contributes to the fine control of cardiac performance on demand, but not cardiac function (30).…”
Section: Sns Abnormality In Patients With a History Of Ventricular Arsupporting
confidence: 72%
See 1 more Smart Citation
“…Those results or ours suggest that SNS abnormality is more sensitive for predicting arrhythmic events than is left ventricular dysfunction or structural heart disease. Our results may support the possibility that SNS activity contributes to the fine control of cardiac performance on demand, but not cardiac function (30).…”
Section: Sns Abnormality In Patients With a History Of Ventricular Arsupporting
confidence: 72%
“…Those results support the close relationship between left ventricular function and SNS activity in patients with ventricular tachyarrhythmia. On the other hand, patients who underwent heart transplantation and had denervated hearts did not show severe left ventricular dysfunction, but about 10% of the patients experienced sudden cardiac death, presumably due to arrhythmia (29), suggesting a direct effect of SNS abnormality (30)(31)(32). In the present study, SNS abnormality increased the occurrence of recurrent ventricular arrhythmia independent of left ventricular dysfunction or structural heart disease.…”
Section: Sns Abnormality In Patients With a History Of Ventricular Arcontrasting
confidence: 41%
“…Sema3a has been identified as the chemorepellent agent inducing growth cone collapse and repelling sympathetic axons in the heart, as opponent of NGF, reported to be required for active sympathetic axon growth and innervation in the heart [Ieda et al, 2004[Ieda et al, , 2007Kuruvilla et al, 2004]. It could be shown that mice targeted with Sema3a or those overexpressing the gene display sudden cardiac death or lethal arrhythmias due to disruption of innervation patterning.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its role within the central neuronal system, SEMA3A is also important for development and plasticity of the peripheral system contributing to cardiac sympathetic innervation, and T-cell migration [Ieda et al, 2004[Ieda et al, , 2007Garcia et al, 2011]. SEMA3A is also distinctively and differentially expressed in spinal cord motor neurons and its signaling controls the timing of motor axon ingrowth to the limb [Cohen et al, 2005;Huber et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…The response of the heart to sympathetic stimulation is modulated by the protein Semaphorin 3a (54). Semaphorin 3a-transgenic mice show catecholamine suprasensitivity and prolonged QT; they die from sudden death.…”
Section: Autonomic Nerve Dysfunction and Sympathetic Overactivitymentioning
confidence: 99%